Midterm Outcomes of Posterior Medial Meniscus Root Tear Repair: A Systematic Review. Issue 2 (February 2022) - Chang, Peter S.; Radtke, Logan; Ward, Patrick; Brophy, Robert H.
Background: Whereas there has been growing interest in surgical repair of posterior medial meniscus root tears (PMMRTs), our understanding of the medium- and long-term results of this procedure is still evolving. Purpose: To report midterm clinical outcomes from PMMRT repairs. Study Design: Systematic review. Methods: A literature review for this systematic analysis was performed in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. We identified studies that reported the results of arthroscopic repair of PMMRTs. Functional and imaging outcomes were reviewed and summarized. Results: In total, 28 studies with a total of 994 patients (83% female) with an overall mean age of 57.1 were included in this review. Clinical outcomes (Lysholm, International Knee Documentation Committee, Hospital for Special Surgery, and Tegner scores) were improved at final follow-up in all studies. Of patients, 49% had radiographic progression of at least 1 grade in the Kellgren-Lawrence scale at a mean follow-up of 4.0 years in 11 studies. Cartilage degeneration had progressed at least 1 grade on magnetic resonance imaging scans in 23% of patients at a mean follow-up of 31.6 months in 4 studies. Conclusion: PMMRT repairs provide a functional benefit with consistent improvements in clinical outcome scores. There is some evidence that PMMRT repair slows the progression of osteoarthritis but does not prevent it at midterm follow-up.